Three New Steriodal Saponins from the Rhizomes of Tupistra chinensis Baker. Issue 3 (2nd March 2023) - He, Xuefeng; Yuan, Xiaofeng; Liu, Yang; Qiu, Pengcheng; Bi, Linlin; Tang, Haifeng; Lu, Yunyang
Abstract: The phytochemical constituent investigation on the 70 % ethanol extract of the rhizomes of Tupistra chinensis Baker resulted in the isolation of three new steroidal saponins which were named tuchinosides A–C (1 –3 ). Their structures were determined by extensive spectrum analysis and chemical evidence, especially 2D NMR and HR‐ESI‐MS techniques. In addition, the cytotoxicity of compounds 1–3 against several human cancer cell lines was evaluated. Abstract :